PENGARUH PENDEKATAN HUMANISTIK TERHADAP MOTIVASI BELAJAR KELAS X MAS KHULAFAUR RASYIDIN MATA PELAJARAN PPKN - Fitriani, Nani; Okianna, Okianna; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of a humanistic approach to learning motivation of class X MIA students of MA Khulafaur Rasyidin Kubu Raya on PPKn subjects. This research used a descriptive quantitative method. The subjects of this research are students of class X MIA A and X MIA B MA Khulafaur Rasyidin Kubu Raya and the data are questionnaire sheets as well as the results of interviews with PPKn teachers and class X students. The results show that there is an influence of the humanistic approach to student learning motivation. Learning motivation divided into 6 indicators with 32 sub indicators showed different motivations, but it can be categorized very high for class X MIA A which is equal to 88.22 while for class X MIA B can be categorized very high at 91.92 %%. Based on the results of the t test in class X MIA A and X MIA B shows the value of t count of 5.980 with a significance level of 0,000 or in other words 0,000 smaller than 0.05 so that Ho is rejected. While based on a simple regression test the sig (2-tailed) value is 0,000. This means that the value of sig (2-tailed) 0,000 <0.05 so that Ho is rejected. Based on the value of t, the value of t count is 6.887> t table 2.07961. From these results, there is an effect of a humanistic approach to student learning motivation so that the variable X has an effect on variable Y. So from that it can be concluded that there is a significant influence between the humanistic approach to student learning motivation.Â Keywords: Humanistic Approach, Motivation, PPKn